2023
DOI: 10.1002/nafm.10895
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Factors Affecting Short‐Term Survival of Two Age‐0 Rainbow Trout Strains in Colorado Streams

Abstract: Both biotic and abiotic factors can influence the survival and growth of age-0 salmonids. Diseases, such as whirling disease, can also affect salmonid demographics and population dynamics. Here, we conducted a supplementary analysis and evaluated specific stream characteristics that may have been responsible for the differences in growth and survival of two whirling disease resistant Rainbow Trout Oncorhynchus mykiss strains observed by Avila et al. (2018). We used regression modeling to analyze the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(114 reference statements)
1
0
0
Order By: Relevance
“…363 Also, many other researches have focused on the mechanism of Rainbow trout temperature stress, 364,365 and it has been proven that the degree Celsius of water is the primary determinant of its short-term survival. 366 Our research further confirmed that when fed with plant oils instead of fish oil, the mode of lipid accumulation of Rainbow trout largely depends on water temperature.…”
Section: Discussionsupporting
confidence: 78%
“…363 Also, many other researches have focused on the mechanism of Rainbow trout temperature stress, 364,365 and it has been proven that the degree Celsius of water is the primary determinant of its short-term survival. 366 Our research further confirmed that when fed with plant oils instead of fish oil, the mode of lipid accumulation of Rainbow trout largely depends on water temperature.…”
Section: Discussionsupporting
confidence: 78%